Optimalisasi Pembelajaran Menulis Persuasi Melalui Model Pembelajaran Multiliterasi di Sekolah Dasar - Reskiyana Lestari Hasibuan; Chandra Chandra; Inggria Kharisma (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Persuasive writing is a skill that students need to master in conveying ideas in a structured and convincing manner. However, initial observations showed that the majority of students had difficulty in developing ideas and constructing logical arguments in persuasive writing. Several factors caused this, 1) lack of student motivation in writing, 2) lack of variation in learning strategies, and 3) limited use of media and learning resources that are relevant to the world of students. This study uses a qualitative-descriptive research method, namely observation which aims to improve students' persuasive writing skills using a multiliteracy learning model that can improve students' understanding and knowledge. The subjects of the study were several fifth grade elementary school children. The results of the interim study showed that the application of a significant multiliteracy learning model can improve students' understanding and ability in writing persuasive texts as indicated by an increase in the average score of students' writing compared to the results of previous studies in persuasive writing.